Simulation of Resources Sharing Architecture (ReSa) between clouds using Java programming - Waqas, Ahmad; Muhammed Yusof, Zulkefli; Shah, Asadullah; Bhatti, Zeeshan; Mahmood , Nadeem (2015)
Cloud computing has been emerged as cost-effective solution to organizations for renting resources. The prime objective is to deliver on-demand resources over the Internet.In this paper, we have implemented the architecture for resource sharing between clouds (ReSA) to connect different clouds that may be under different rule, policies, management and ownership. The ultimate task is to enable clouds to borrow resource from other connected clouds to fulfill the demand of the client. We have demonstrated the implementation using java socket programing and test-bed. We further analyzed the average waiting time for resources when they are borrowed from other cloud.